The influence of principal managerial ability and bos fund management on the performance of leading teachers at elementary schools in solok regency - Titony Tanjung; Fadriati Fadriati; David David; Lili Ramahdani (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
This study was motivated by the suboptimal managerial role of school principals, limited leadership support, and the lack of transparency in the management of the School Operational Assistance (BOS) funds, which have hindered support for the innovative programs of teacher leaders as agents of change in schools. The study aims to determine the extent to which the managerial capabilities of school principals and the management of BOS funds influence the performance of teacher leaders, both partially and simultaneously. The research design employed is a field study using a quantitative approach with multiple linear regression. The study population consists of 335 teacher-leaders at public elementary schools in Solok Regency, with a sample of 183 participants determined using the Slovin formula and proportional random sampling. Data were collected via questionnaires and analyzed using multiple regression with the aid of IBM SPSS Statistics 26. The results indicate that the principal’s managerial competence has a significant effect on the performance of teacher leaders. Conversely, the management of BOS funds does not have a significant effect when considered partially. However, when considered simultaneously, both variables have a significant effect on the performance of teacher leaders